Effect of nanodiamond additives on the structure and gas‐transport properties of a poly(phenylene–isophtalamide) matrix. Issue 23 (22nd February 2018) - Avagimova, Natalia; Polotskaya, Galina; Toikka, Alexander; Pulyalina, Alexandra; Morávková, Zuzana; Trchová, Miroslava; Pientka, Zbyněk
ABSTRACT: Nanodiamonds (NDs) are specific carbon nanoparticles approximately 5 nm in diameter with a large and accessible surface containing functional groups. Poly(phenylene–isophtalamide) (PA)–ND composites were prepared by solid‐phase dispersal and used for dense film formation. The PA–ND composites were analyzed by Fourier transform infrared spectroscopy. The membrane structure was determined on the basis of density measurement and morphological study by atomic force microscopy. The gas‐transport properties were measured over a wide range of temperatures from 30 to 100 °C for the following series of penetrants: H2, N2, O2, and CO2 . The experimental data of gas permeability were compared with the permeability values calculated from Maxwell's model. Data on the permeability and diffusion coefficients were used to calculate the activation energies. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46320. Abstract :